Answer:
x = 1
y = 7
Explanation:
Two equations, two unknowns. We know that y = 7x so we can substitute that into the first equation to get:
![-5+2\left(7x\right)=9](https://img.qammunity.org/2022/formulas/mathematics/college/c7pctmse6wyog48w0tpvqy2xn6udx8fnm7.png)
![-5+14x=9](https://img.qammunity.org/2022/formulas/mathematics/college/37ccxztg4ofeb8pj0ksgsgxn3feet2mzx8.png)
![14x=14](https://img.qammunity.org/2022/formulas/mathematics/college/syoi34qgc7cl4uqel42wud7tqsegfkiqyk.png)
This gives us x = 1.
Now plug this bag into either equation to find y, I will use the second since it's easier:
y = 7(1) = 7